20‐1: Invited Paper: Towards Deep‐Blue Materials with Efficient Triplet Harvesting. Issue 1 (30th May 2018) - Krotkus, Simonas; Wong, Michael Y.; Hedley, Gordon; Jaricot, Marie; Cordes, David B.; Slawin, Alexandra M. Z.; Murawski, Caroline; Gather, Malte C.; Olivier, Yoann; Beljonne, David; Zysman-Colman, Eli; Samuel, Ifor D. W.
Abstract : The development of materials for deep blue OLEDs will be presented. A novel donor‐acceptor TADF compound comprising oxadiazole acceptor units was studied. The emission is tuned towards deep‐blue by tuning the acceptor strength, and TADF is demonstrated. Finally, the results are compared with model sky‐blue emitter 2CzPN.